Some observations on fertility of goats after synchronization of estrus and artificial insemination - ΕΛΕΥΘΕΡΙΟΥ Ε.; ΚΟΥΤΣΟΥΡΗΣ Χ. (Journal of the Hellenic Veterinary Medical Society, 2019)
1. Oestrus synchronization was induced in 15, seven months old (group 1), 24, one and half years old (group II) and 72 mature goats (group III) by vaginal sponges containing 50mg MAP, inserted For 14 days and 500 U. I PMS at the time of sponges removal. AU animals were inseminated blindly 48 and 72 hours after sponges removal (200 million total spermatozoa per A. I. ). 2. The percentage of kidding was 60,0%, 58,3% and 61,1% and the average litter size was 1,77, and 1,95 in the I, II and III group, respectively. 3. The animals of the second group which had attained a liveweight of 35 Kgs had a lower conception rate (16,6%) than the the remainder of the same group (72,0%). 4. It is concluded that kids of seven month old and yearling goats respond well to the synchronization treatment